Palladium(II) Complex derived from Harmaline; an Alkaloid Isolated from Peganum harmala Seeds: Synthesis, characterization and Cytotoxic Activity - A.K. Al-Allaf, Talal; J. Rashan, Luay (Asian Journal of Chemistry, 2010)
The 1 : 1 molar ratio reaction of trans-[Pd(DMSO)2CI2] (I)with harmaline, the naturally occuring alkaloid, isolated fromPeganum harmala seeds, in non-aqueous solvent, was found to give,mainly, the monomer trans-[Pd(harmaline)(DMSO)CI2] (II) as amajor component and the dimer [Pd(harmaline)Cl2]2 (Ill) as aminor one. The monomer (II) can be formed, as a single product,either by the direct reaction between I and harmaline in DMSO orby dissolving II in DMSO. In both cases the pure monomer (II)can be precipitated from its DMSO solution by the addition of 0.05M HCl. The complexes have been characterized by their C, H, Nanalysis, 1H, 13C, IR and mass spectroscopic methods. Themonomer (Il) has been tested for its cytotoxic activity againstseveral tumour cell lines, i.e., P388, L1210, K562, Raji, HeLa, RDand Hep-2. This activity was compared with those of referencestandards, cisplatin, carboplatin and 5-tluorouracil (5-FU).